THE IMPORTANCE OF PHYSICAL EDUCATION CLASSES FOR THE PSYCHOMOTOR DEVELOPMENT OF STUDENTS - Rodrigues da Silva, Marcos André; Almeida de Souza, Katrice (RENEF, 2023)
The term Psychomotricity is defined as any driving action, attitude or pattern of behavior that, under the influence of mental processes, integrates and combines these processes with motor aspects, such as elements that influence behavior. The aim of this article is to understand the importance of Physical Education classes for the psychomotor development of students. Prove the importance of psychomotor development in school education with the contribution of the Physical Education Professional and understand the way in which the school promotes stimuli to develop psychomotricity in its students. This is a basic and qualitative research that will use bibliographical research. Psychomotricity works with the child’s motor, cognitive and emotional aspects. In this way, the psychomotor areas, when properly worked on, favor the individual’s overall development. Physical Education classes at school have great importance in the psychomotor training of the individual, being essential for their growth. It is concluded that psychomotricity, together with playful strategies, has developed an extremely important role in recent years, as it is scientifically proven that its use linked to the teaching process is essential for the intellectual and motor development of children.